2015
DOI: 10.1016/j.prevetmed.2015.02.016
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study on the prevalence and risk factors for foot and limb lesions in piglets on commercial farms in Ireland

Abstract: (2015) A crosssectional study on the prevalence and risk factors for foot and limb lesions in piglets on commercial farms in Ireland. Preventive Veterinary Medicine, Volume 119 (Number 3-4). pp. 162-171. Permanent WRAP url: http://wrap.warwick.ac.uk/67195 Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes this work of researchers of the University of Warwick available open access under the following conditions. Copyright © and all moral rights to the version of the paper presented here belon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The prevalence of carpal abrasions and lameness in piglets increases with age (Quinn et al, 2015). In our study we included piglet age as a covariate in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of carpal abrasions and lameness in piglets increases with age (Quinn et al, 2015). In our study we included piglet age as a covariate in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Injury is another widespread problem associated with modern pork production (54) and was the most observed clinical sign observed in Danish finisher pigs (50). The prevalence of foot and limb lesions in preweaning piglets on commercial farms in Ireland ranged from 0 to 100% (56), and the overall prevalence on commercially representative pig farms in England was 39.6% (57). One study showed a high prevalence of lesions on the limbs (93%), body (20%) (58), and feet (59) of commercial sows in England.…”
Section: Sources Of Pain In Pigsmentioning
confidence: 99%
“…Bonde [ 59 ] recorded decubitus ulcers in 17% of lactating sows. Quinn et al [ 60 ], who studied the presence of limb lesions in unweaned piglets, reported frequent sole bruises (61.5%), abrasions on the limbs (55.7%) and sole erosion (34.1%). Harley et al [ 61 ], who analyzed findings at pig slaughterhouses, revealed that 16% of slaughtered pigs were affected by severe bruises and 44% had bursitis in the hind limb.…”
Section: Discussionmentioning
confidence: 99%
“…In pigs, the type of floors also has a major effect on their limb health. The greater prevalence of limb lesions resulting from housing on a hard floor was reported in piglets [ 60 ], in finisher pigs [ 35 ] and in sows [ 35 , 58 , 81 , 82 ]. Floors could be a serious problem for all categories of pigs in intensive farming but they are more frequently used in sows and piglets.…”
Section: Discussionmentioning
confidence: 99%